A bolu: costruzioni patrimoniali in Sardegna - Ignazio Macchiarella (In Situ)
As elsewhere, the oral musical tradition in Sardinia went through a period of relative crisis after the Second World War, with the spread of new media. The 1980s saw a general reversal of this trend, following a rediscovery of the area in terms of its identity. In 2005, UNESCO included the cantu a tenore in its list of Masterpieces of the Oral and Intangible Heritage of Humanity. My essay aims first of all to describe the scenario in which the UNESCO intervention took place, the (somewhat controversial) methods with which it was carried out and the results that emerged, both in the context of the musical practice that was the subject of the proclamation, and in that of other musical practices not taken into account by the recognition, but of equal cultural value to the island's inhabitants. Emphasis is placed on the significant initiatives undertaken by groups of Canto a tenore in collaboration with representatives of other traditional practices (canto a cuncordu, launeddas, improvised poetry, guitar-accompanied singing) who have promoted original actions of self-heritagization, culminating, in 2015, in the creation of an association made up of musicians from different traditional practices. Through initiatives funded by the Regional Government of Sardinia, this association puts forward its own idea of heritage and authenticity. In the light of the situation under consideration, the essay offers theoretical and methodological reflections on the role of the ethnomusicologist and the impact of UNESCO's action on oral tradition musical practices.